THE IMPLEMENTATION OF SHADOWING TEACHING TECHNIQUES TO IMROVE STUDENTS’ SPEAKING ABILITY AT SMAN 2 SIDRAP - Andi Tenri Bali Yahya; Erwin Akib; Ilmiah (FKIP Unismuh Makassar, 2021)
This research aimed at finding out students’ speaking ability using shadowing techniques at the First Grade of SMAN 2 Sidrap This research uses pre-experimental research. Researcher have conducted treatment consisting of six meetings. The population of this research is the first-grade students at SMAN 2 Sidrap. Researcher used purposive sampling technique. The research instrument was a speaking test. The research findings indicated that achievement of the first grade of SMAN 2 Sidrap was improved after using shadowing techniques. It was proven by mean score in terms of content in pre-test was 58 and post-test was 77. The improvement of the content was 0.020%. It means that there was significant difference between post-test and pre-test. Based on the research finding, the researcher concluded that teaching English by using shadowing techniques could improve the students’ Speaking ability.